Ethnic Church Meets Megachurch : Indian American Christianity in Motion - Prema A. Kurien (NYU Press, 2017)
Winner, 2018 Section on Asia and Asian America Book Award presented by the American Sociological Association Traces the religious adaptation of members of an important Indian Christian church– the Mar Thoma denomination – as they make their way in the United States. This book exposes how a new paradigm of ethnicity and religion, and the megachurch phenomenon, is shaping contemporary immigrant religious institutions, specifically Indian American Christianity. Kurien draws on multi-site research in the US and India to provide a global perspective on religion by demonstrating the variety of ways that transnational processes affect religious organizations and the lives of members, both in the place of destination and of origin. The widespread prevalence of megachurches and the dominance of American evangelicalism created an environment in which the traditional practices of the ancient South Indian Mar Thoma denomination seemed alien to its American-born generation. Many of the young adults left to attend evangelical megachurches. Kurien examines the pressures church members face to incorporate contemporary American evangelical worship styles into their practice, including an emphasis on an individualistic faith, and praise and worship services, often at the expense of maintaining the ethnic character and support system of their religious community. Kurien's sophisticated analysis also demonstrates how the forces of globalization, from the period of colonialism to contemporary out-migration, have brought about tremendous changes among Christian communities in the Global South. Wide in scope, this book is a must read for an audience interested in the study of global religions and cultures.